Analisis Tingkat Risiko Dan Penerapan Smk3 Pada Proyek Pembangunan Rumah Sakit Umum Daerah Mangusada Badung - I Ketut Sutapa; I Wayan Suasira; Putu Hermawati; I Putu Arya Setya Dharma (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
Every construction project, whether high-tech or simple, has risks in the implementation process. there-fore it is necessary to establish a Project Safety Management (PSM), to minimize the risk of occupational safety and health (OSH) of construction project. However there are still many construction companies that are lacking in identifying risks of occupational safety and health(OSH) of construction project and implementing an occupational Project Safety Management (PSM)) in the process of implementing a con-struction project. The purpose of this study was to determine the level of risk occupational safety and health based on existing risk factors, and to measure the application level of SMK3 in a construction pro-ject. In this study, the object of the case study was the construction project of the Mangusada Badung Regional General Hospital, at the time of finishing work. After carrying out risk identification, 4 risk fac-tors are obtained, namely human, material, equipment and environmental factors. then the results of the identification are processed, and the level of risk obtained from the implementa-tion of the Mangusada Badung Regional General Hospital Development Project is included in the Medium Category, with a risk value of 6. Meanwhile, the implementation of the Project Safety Management (PSM) of the Mangusada Badung Regional General Hospital Construction Project was included in the good cate-gory with a total application value of 83%. Hopefully this research will serve as a reference in identifying occupational safety and health (OSH) risks, and a reference in implementing the Occupational Project Sfety Manajemen (PSM).